Laxative Effect of Lacticaseibacillus rhamnosus Glory LG12: from the Perspective of the Stem Cell Factor/C-kit Signaling Pathway - XIANG Fangqin, LI Yuxing, LI Bailiang (Shipin Kexue)
Purpose: To explore the laxative effect of Lacticaseibacillus rhamnosus Glory LG12 from the perspective of the stem cell factor (SCF)/C-kit signaling pathway. Methods: Male ICR mice were randomly divided into five groups: control, model, low- (1.5 × 106 CFU/mouse), medium- (1.5 × 107 CFU/mouse), and high- (1.5 × 108 CFU/mouse) dose L. rhamnosus Glory LG12. After 15 continuous days of gavage, all mice were further gavaged with loperamide hydrochloride suspension (4 mg/kg) to establish a mouse model of constipation. Body mass, the time taken until the first black stool excretion, the number and mass of black stool within 5 hours, small intestinal transit rate, serum levels of gastrointestinal regulatory peptides and inflammatory cytokines, colonic SCF and C-kit transcription levels were measured, and colonic pathology was examined. Results: Compared with the model group, medium- and high-dose L. rhamnosus Glory LG12 significantly reduced the time taken until the first black stool excretion (P < 0.001), increased the number and mass of black stools within 5 h (P < 0.01 and P < 0.001, respectively), and improved the ink propulsion rate in the small intestine (P < 0.001). In addition, both treatments elevated the serum levels of motilin (MTL), gastrin (Gas), substance P (SP), and interleukin 10 (IL-10), reduced the levels of endothelin-1 (ET-1), somatostatin (SS), vasoactive intestinal peptide (VIP), and IL-6, up-regulated the relative mRNA expression of SCF and C-kit in colonic tissue was (P < 0.01, P < 0.001), and restored damaged colonic barrier. Conclusion: L. rhamnosus Glory LG12 promotes gastrointestinal motility by affecting the release of gastrointestinal regulatory peptides and inflammatory cytokines through the modulation of the SCF/C-kit signaling pathway, thereby alleviating constipation symptoms.